Manual therapy and exercise for lateral elbow pain - Wallis, Jason A; Bourne, Allison M; Jessup, Rebecca L; Johnston, Renea V; Frydman, Aviva; Cyril, Sheila; Buchbinder, Rachelle (Cochrane database of systematic reviews, 2024)
Manual therapy and prescribed exercises are often provided together or separately in contemporary clinical practice to treat people with lateral elbow pain. To assess the benefits and harms of manual therapy, prescribed exercises or both for adults with lateral elbow pain. We searched the databases CENTRAL, MEDLINE and Embase, and trial registries until 31 January 2024, unrestricted by language or date of publication. We included randomised or quasi-randomised trials. Participants were adults with lateral elbow pain. Interventions were manual therapy, prescribed exercises or both. Primary comparators were placebo or minimal or no intervention. We also included comparisons of manual therapy and prescribed exercises with either intervention alone, with or without glucocorticoid injection. Exclusions were trials testing a single application of an intervention or comparison of different types of manual therapy or prescribed exercises. Two review authors independently selected studies for inclusion, extracted trial characteristics and numerical data, and assessed study risk of bias and certainty of evidence using GRADE. The main comparisons were manual therapy, prescribed exercises or both compared with placebo treatment, and with minimal or no intervention. Major outcomes were pain, disability, heath-related quality of life, participant-reported treatment success, participant withdrawals, adverse events and serious adverse events. The primary endpoint was end of intervention for pain, disability, health-related quality of life and participant-reported treatment success and final time point for adverse events and withdrawals. Twenty-three trials (1612 participants) met our inclusion criteria (mean age ranged from 38 to 52 years, 47% female, 70% dominant arm affected). One trial (23 participants) compared manual therapy to placebo manual therapy, 12 trials (1124 participants) compared manual therapy, prescribed exercises or both to minimal or no intervention, six trials (228 participants) compared manual therapy and exercise to exercise alone, one trial (60 participants) compared the addition of manual therapy to prescribed exercises and glucocorticoid injection, and four trials (177 participants) assessed the addition of manual therapy, prescribed exercises or both to glucocorticoid injection. Twenty-one trials without placebo control were susceptible to performance and detection bias as participants were not blinded to the intervention. Other biases included selection (nine trials, 39%, including two quasi-randomised), attrition (eight trials, 35%) and selective reporting (15 trials, 65%) biases. We report the results of the main comparisons. Manual therapy versus placebo manual therapy Low-certainty evidence, based upon a single trial (23 participants) and downgraded due to indirectness and imprecision, indicates manual therapy may reduce pain and elbow disability at the end of two to three weeks of treatment. Mean pain at the end of treatment was 4.1 points with placebo (0 to 10 scale) and 2.0 points with manual therapy, MD -2.1 points (95% CI -4.2 to -0.1). Mean disability was 40 points with placebo (0 to 100 scale) and 15 points with manual therapy, MD -25 points (95% CI -43 to -7). There was no follow-up beyond the end of treatment to show if these effects were sustained, and no other major outcomes were reported. Manual therapy, prescribed exercises or both versus minimal intervention Low-certainty evidence indicates manual therapy, prescribed exercises or both may slightly reduce pain and disability at the end of treatment, but the effects were not sustained, and there may be little to no improvement in health-related quality of life or number of participants reporting treatment success. We downgraded the evidence due to increased risk of performance bias and detection bias across all the trials, and indirectness due to the multimodal nature of the interventions included in the trials. At four weeks to three months, mean pain was 5.10 points with minimal treatment and manual therapy, prescribed exercises or both reduced pain by a MD of -0.53 points (95% CI -0.92 to -0.14, I = 43%; 12 trials, 1023 participants). At four weeks to three months, mean disability was 63.8 points with minimal or no treatment and manual therapy, prescribed exercises or both reduced disability by a MD of -5.00 points (95% CI -9.22 to -0.77, I = 63%; 10 trials, 732 participants). At four weeks to three months, mean quality of life was 73.04 points with minimal treatment on a 0 to 100 scale and prescribed exercises reduced quality of life by a MD of -5.58 points (95% CI -10.29 to -0.99; 2 trials, 113 participants). Treatment success was reported by 42% of participants with minimal or no treatment and 57.1% of participants with manual therapy, prescribed exercises or both, RR 1.36 (95% CI 0.96 to 1.93, I = 73%; 6 trials, 770 participants). We are uncertain if manual therapy, prescribed exercises or both results in more withdrawals or adverse events. There were 83/566 participant withdrawals (147 per 1000) from the minimal or no intervention group, and 77/581 (126 per 1000) from the manual therapy, prescribed exercises or both groups, RR 0.86 (95% CI 0.66 to 1.12, I = 0%; 12 trials). Adverse events were mild and transient and included pain, bruising and gastrointestinal events, and no serious adverse events were reported. Adverse events were reported by 19/224 (85 per 1000) in the minimal treatment group and 70/233 (313 per 1000) in the manual therapy, prescribed exercises or both groups, RR 3.69 (95% CI 0.98 to 13.97, I = 72%; 6 trials). Low-certainty evidence from a single trial in people with lateral elbow pain indicates that, compared with placebo, manual therapy may provide a clinically worthwhile benefit in terms of pain and disability at the end of treatment, although the 95% confidence interval also includes both an important improvement and no improvement, and the longer-term outcomes are unknown. Low-certainty evidence from 12 trials indicates that manual therapy and exercise may slightly reduce pain and disability at the end of treatment, but this may not be clinically worthwhile and these benefits are not sustained. While pain after treatment was an adverse event from manual therapy, the number of events was too small to be certain.